Electrically controlled drug release metal organic framework based composite application as well as preparation method and application thereof
By preparing an electro-controlled drug release metal-organic framework composite patch using UiO-N+@SWCNT loaded with drugs and P(PLMA-AM-DAC) hydrogel, the problems of low drug release efficiency and poor patient compliance were solved, achieving precise drug control and efficient transdermal delivery, thus improving the treatment effect of psoriasis.
Patent Information
- Application Number
- CN202511528100.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-10-24
- Publication Date
- 2026-01-23
AI Technical Summary
Existing electrostimulation-controlled drug release technology suffers from limited drug loading efficiency, poor patient compliance, and a lack of precise control over drug release, especially in the treatment of psoriasis where it is difficult to adjust the release rate and timing according to the patient's needs.
UiO-N+@SWCNT loaded with drugs was prepared by a solvothermal method and then combined with P(PLMA-AM-DAC) hydrogel and flexible printed circuit board to form an electro-controlled drug release metal-organic framework composite patch. The redox state switching of the drug was achieved by voltage regulation, and combined with the physical permeation-enhancing effect of electrostimulation, an integrated electrostimulation transdermal drug delivery patch was constructed.
It significantly improves the efficiency of transdermal drug delivery, enhances treatment adherence, and can controllably release drugs in response to electrical stimulation. It also combats bacterial infection and inflammation, promotes chronic wound repair, and improves the treatment effect of psoriasis.
Smart Images

Figure CN121371235A_ABST
Abstract
Description
TECHNICAL FIELD
[0001] The present application belongs to the technical field of medical materials, and particularly relates to an electrically controlled drug release metal organic framework-based composite patch as well as a preparation method and application thereof. BACKGROUND
[0002] Psoriasis is a high-incidence proliferative chronic inflammatory skin disease, and 1-3% of people worldwide suffer from this disease. It presents symptoms such as skin peeling, swelling, itching, inflammatory pain, etc., which brings great inconvenience to the life of patients. Local ointment coating administration is the most common treatment method for skin diseases, but it is reported that only 10-20% or less of the drug can penetrate the skin. In addition, the stratum corneum of psoriasis patients is thicker, and it is more difficult to absorb drugs, which seriously affects the treatment effect of ointment. Electric stimulation therapy is a new method for treating skin diseases in recent years, which not only can promote the drug to overcome the stratum corneum barrier and enter the body, but also can realize on-demand release of the drug in response to electric stimulation.
[0003] At present, the electric stimulation controlled drug release technology mainly relies on electric responsive materials. Common electric responsive materials include conductive polymers and hydrogels, etc. Conductive polymers such as polypyrrole and polyaniline have excellent electrochemical properties, and can realize the loading and release of drugs through electric switching between the oxidized state and the reduced state. Although conductive polymers have been fully studied in drug delivery, they still face the challenges of limited drug loading efficiency and poor patient compliance in practical application. As a hydrophilic matrix, hydrogel can load drugs and respond to external stimuli, but its response speed and stability still need to be further improved. In addition, traditional electric responsive materials often lack precise control mechanism in the process of drug release. The rate and timing of drug release are difficult to adjust according to the actual needs of patients, which to some extent affects the treatment effect. SUMMARY
[0004] In view of the above problems, the purpose of the present application is to provide an electrically controlled drug release metal organic framework-based composite patch as well as a preparation method and application thereof.
[0005] The technical content of the present application is as follows: The present application provides a preparation method of an electrically controlled drug release metal organic framework-based composite patch, comprising the following steps: 1) Preparation of UiO-N + @SWCNT The single-walled carbon nanotube (SWCNT), Zr 4+ and 2,2'-dipyridyl-5,5'-dicarboxylate are combined, UiO-67 is grown in situ on SWCNT by solvothermal method to prepare UiO@SWCNT, and then the dipyridyl part is N-methylated with methyl triflate to obtain UiO-N + @SWCNT; 2) Preparation of UiO-N + @SWCNT loaded with drug (UiO-N) + @SWCNT / Drug) Prepare the drug solution by adding UiO-N + @SWCNT is placed in the drug solution to obtain UiO-N + @SWCNT / Drug; The drugs include conventionally loadable small molecule anionic drugs; Specifically, the drug includes one or more of dexamethasone sodium phosphate, fluorescein sodium, and diclofenac sodium; 3) Preparation of UiO-N + @SWCNT / Drug membrane electrode UiO-N + @SWCNT / Drug material and conductive agent are prepared into a slurry in polyvinylpyrrolidone / N-methylpyrrolidone solution, vortexed, and then the slurry is drop-coated onto a polytetrafluoroethylene mold and dried to obtain a membrane electrode. The conductive agent includes Ketjen Black; 4) Preparation of P(PLMA-AM-DAC) hydrogel A PBS solution of phenyl (2,4,6-trimethylbenzoyl) lithium phosphate (LAP) was prepared, and then methacrylyl polylysine (PLMA), acrylamide (AM), and acryloyloxyethyltrimethylammonium chloride (DAC) were added. After dissolving by shaking at room temperature, the solution was sterilized using a 0.22 μm sterile needle filter. The solution was then injected into a polytetrafluoroethylene mold and irradiated under a UV-LED 405 nm light source until completely cured to obtain P(PLMA-AM-DAC) hydrogel. LAP, as a photoinitiator, is used at a concentration of 0.25% (w / v) in phosphate buffer solution; PLMA, as an antibacterial peptide, is used at a concentration of 2% (w / v); AM, which can be polymerized to enhance mechanical properties, is used at a concentration of 30% (w / v); and DAC, which can improve conductivity and also has antibacterial function due to its positive charge, is used at concentrations of 0%, 2%, and 5% (w / v), respectively. 5) Preparation of electro-controlled drug release metal-organic framework composite patches UiO-N + The @SWCNT / Drug membrane electrode is attached to the P(PLMA-AM-DAC) hydrogel, and then covered with a flexible printed circuit board to assemble an electro-controlled drug release metal-organic framework composite patch.
[0006] The present invention also provides an electro-controlled drug release metal-organic framework-based composite dressing obtained by the above preparation method.
[0007] The application also provides an application of the electrically controlled drug release metal organic framework-based composite patch in the preparation of a psoriasis treatment product.
[0008] The application has the following advantages: The preparation method of the electrically controlled drug release metal organic framework-based composite patch of the application comprises in-situ growth of UiO-67 on SWCNT by a solvothermal method to prepare UiO@SWCNT, and N-methylation of the bipyridine part by using methyl trifluoromethanesulfonate to obtain UiO-N + @SWCNT, loading of a small molecule drug to obtain UiO-N + @SWCNT / Drug, a P(PLMA-AM-DAC) hydrogel, and a flexible printed circuit board to form the electrically controlled drug release metal organic framework-based composite patch, which is connected to a mobile phone APP through a Bluetooth module to construct an integrated electric stimulation transdermal drug delivery patch. The flexible wearable property of the system makes it more comfortable and convenient, and helps to improve the treatment compliance and quality of life of patients, and provides an intelligent solution for the treatment of chronic skin diseases.
[0009] The electrically controlled drug release metal organic framework-based composite patch of the application can realize drug controlled release by regulating the redox state of the cationic MOFs (UiO-N + @SWCNT) through voltage, and can significantly improve the transdermal drug delivery efficiency by combining the electric stimulation physical penetration effect, for example, the release amount of dexamethasone sodium phosphate is 239 μg / mg under the stimulation of-0.6 V for 10 minutes, which is significantly higher than the passive release (15 μg / mg). + @SWCNT) into a membrane electrode, combining the antibacterial hydrogel P(PLMA-AM-DAC) and the flexible circuit board (FPC), can controllably release the drug in response to electric stimulation, resist bacterial infection and inflammation, and accelerate the repair of chronic wounds, and has a mild effect, so that the affected area can be healed early, and the patient compliance is improved. BRIEF DESCRIPTION OF DRAWINGS
[0010] Figure 1 X-ray diffraction patterns of different MOF powders; Figure 2 Transmission electron microscope images of different MOF powders; Figure 3 Zeta images of different MOF powders; Figure 4 N2 adsorption-desorption isotherms of different MOF powders; Figure 5 A schematic diagram of the construction of the integrated electric stimulation transdermal drug delivery patch; Figure 6 A cyclic voltammogram of UiO-N + @SWCNT; Figure 7 Figure for drug accumulation and release of MOF@Drug at different applied voltages and MOF@Drug controllable on-demand drug delivery in "on-off" mode; Figure 8 Figure for in vitro antibacterial effect of P(PLMA-AM-DAC) hydrogel; Figure 9 Figure for cell compatibility of MOF powder and P(PLMA-AM-DAC) hydrogel; Figure 10 Figure for treatment effect of the electro-controlled drug release metal-organic framework-based composite patch on the skin of psoriasis mice; Figure 11 Figure for skin tissue section photos dyed with hematoxylin and eosin (H&E) after 8 days of treatment. DETAILED DESCRIPTION
[0011] The application will be described in further detail below with specific implementation cases and accompanying drawings. It should be understood that these examples are only used to illustrate the application and are not used to limit the protection scope of the application. After reading the application, those skilled in the art can make various equivalent modifications of the application, which fall within the scope defined by the appended claims.
[0012] Unless otherwise specified, all raw materials and reagents of the application are conventional market raw materials and reagents.
[0013] In the application, the UiO-N + The MOF@SWCNT is prepared by using zirconium-based metal-organic framework UiO-67 as a matrix and methyl triflate to N-methylate the bipyridine part of the UiO-67; The preparation process of the UiO-67 is a commonly known preparation process of the UiO-67 in the technical field, for example, the UiO-67 is prepared by using the solvothermal synthesis method described in the prior art. Since the UiO-67 is a porous crystalline material formed by coordination of zirconium ions and 2,2'-bipyridine-5,5'-dicarboxylate, based on the principle of the application, the selection of the preparation process has little effect on the performance of the final prepared product, and those skilled in the art can select a suitable preparation process according to the current experimental conditions or refer to the prior art. In order to better illustrate the application, a reference technical solution is provided, which is specifically shown in step 1) in Example 1.
[0014] Example 1 Preparation of an electro-controlled drug release metal-organic framework-based composite patch 1) Preparation of cationic metal-organic framework material UiO-N + @SWCNT A solution: 10 mg of carboxylated SWCNT (5-30 μm) was ultrasonically dispersed in 20 mL of N,N-dimethylformamide, and then 45 mg (0.19 mmol) of ZrCl4 was added and ultrasonically dispersed.
[0015] B solution: 45 mg (0.18 mmol) of 2,2'-dipyridyl-5,5'-dicarboxylic acid was ultrasonically dissolved in 20 mL of N,N-dimethylformamide and 0.36 mL of triethylamine.
[0016] B solution was added to A solution, 2.25 mL of glacial acetic acid was added, ultrasonically stirred for 10 min, and heated and stirred at 85°C for 9 h. After the reaction solution was cooled, the obtained solid was centrifuged, washed with N,N-dimethylformamide, and vacuum dried at 150°C for 2 h to obtain UiO@SWCNT. 50 mg of UiO@SWCNT was ultrasonically dispersed in 1 mL of methyl trifluoromethanesulfonate, stirred at room temperature for 24 h, the obtained solid was centrifuged and washed with ethanol, and vacuum dried at 80°C for 2 h to obtain UiO-N + @SWCNT.
[0017] 2) UiO-N + @SWCNT loaded dexamethasone sodium phosphate Before loading the drug, UiO-N + @SWCNT was vacuum dried at 60°C for 6 h.
[0018] A dexamethasone sodium phosphate solution having a concentration of 2 mg / mL was prepared using ultrapure water, 20 mg of UiO-N + @SWCNT was ultrasonically dispersed in the dexamethasone sodium phosphate solution, stirred at room temperature for 24 h, washed with ultrapure water by centrifugation, and dried at 60°C, and the obtained material was named MOF@Dex.
[0019] 3) Preparation of UiO-N + @SWCNT / Drug membrane electrode 300 mg of UiO-N + @SWCNT / Drug material having a concentration of 1 mg / 30 μL and 100 mg of Ketjen black were made into a slurry in a polyvinylpyrrolidone / N-methylpyrrolidone solution (150 mg / 9 mL), and vortexed. Then, the slurry was drop-coated on a polytetrafluoroethylene mold, and dried at 60°C to obtain a membrane electrode having a diameter of 10 mm; 4) Preparation of P(PLMA-AM-DAC) hydrogel Lithium phenyl(2,4,6-trimethylbenzoyl)phosphinate (LAP) was dissolved in a 0.01 M phosphate buffer to obtain a 0.25% (w / v) LAP solution.
[0020] 2% (w / v) of methacrylated polylysine (PLMA), 30% (w / v) of acrylamide (AM) were added into the LAP solution, which was dissolved by shaking at room temperature and sterilized by 0.22 μm sterile needle filter, and then the solution was injected into a polytetrafluoroethylene mold, irradiated under a UV-LED 405 nm light source for 30 s to completely solidify, and the obtained hydrogel was named as PLAm.
[0021] 5) Preparation of an electro-controlled drug release metal-organic framework-based composite patch The above-prepared hydrogel was added dropwise on a membrane electrode (10 mm) so that the hydrogel had a diameter of 17 mm, and the flexible printed circuit board had a size of 40 mm x 15 mm, covering the flexible printed circuit board, i.e., assembled into an electro-controlled drug release metal-organic framework-based composite patch.
[0022] Example 2 Preparation of an electro-controlled drug release metal-organic framework-based composite patch 1) Preparation of cationic metal-organic framework material UiO-N + @SWCNT The operation was the same as in Example 1.
[0023] 2) UiO-N + @SWCNT loaded with fluorescein sodium Before loading the drug, UiO-N + @SWCNT was vacuum dried at 60°C for 6 h.
[0024] A fluorescein sodium solution with a concentration of 2 mg / mL was prepared with ultrapure water, and 20 mg of UiO-N + @SWCNT was ultrasonically dispersed in the fluorescein sodium solution, stirred at room temperature for 24 h, washed by centrifugation with ultrapure water, and dried at 60°C, and the obtained material was named as MOF@FLS.
[0025] 3) Preparation of UiO-N + @SWCNT / Drug membrane electrode The operation was the same as in Example 1. 4) Preparation of P(PLMA-AM-DAC) hydrogel Lithium phenyl(2,4,6-trimethylbenzoyl)phosphinate (LAP) was dissolved in a 0.01M phosphate buffer to obtain a 0.25% (w / v) LAP solution.
[0026] A solution of 2% (w / v) methacrylated polylysine (PLMA), 30% (w / v) acrylamide (AM) and 2% (w / v) of acryloyloxyethyl trimethylammonium chloride (DAC) was added to the LAP solution, which was dissolved by shaking at room temperature and sterilized using a 0.22 pm sterile needle filter. The solution was injected into a polytetrafluoroethylene mold, irradiated under a UV-LED 405 nm light source for 30 s to complete the solidification, and the resulting hydrogel was named PLAm-DAC2.
[0027] 5) Preparation of electro-controlled drug release metal-organic framework-based composite patch The operation was the same as in Example 1.
[0028] Example 3 Preparation of an electro-controlled drug release metal-organic framework-based composite patch 1) Preparation of cationic metal-organic framework material UiO-N + @SWCNT The operation was the same as in Example 1.
[0029] 2) UiO-N + @SWCNT loaded with diclofenac sodium Before loading the drug, UiO-N + @SWCNT was vacuum dried at 60 °C for 6 h.
[0030] A solution of diclofenac sodium with a concentration of 2 mg / mL was prepared with anhydrous ethanol. 20 mg of UiO-N + @SWCNT was ultrasonically dispersed in the diclofenac sodium solution, stirred at room temperature for 24 h, washed by centrifugation with anhydrous ethanol, and vacuum dried overnight at room temperature. The resulting material was named MOF@DS.
[0031] 3) Preparation of UiO-N + @SWCNT / Drug film electrode The operation was the same as in Example 1. 4) Preparation of P(PLMA-AM-DAC) hydrogel Lithium phenyl(2,4,6-trimethylbenzoyl)phosphinate (LAP) was dissolved in a 0.01 M phosphate buffer to obtain a 0.25% (w / v) LAP solution.
[0032] 2% (w / v) of methacrylamide polylysine (PLMA), 30% (w / v) of acrylamide (AM) and 5% (w / v) of acryloyloxyethyltrimethylammonium chloride (DAC) were added to the LAP solution. After dissolving by shaking at room temperature, the solution was sterilized using a 0.22 μm sterile needle filter and injected into a polytetrafluoroethylene mold. The solution was then irradiated under a UV-LED 405 nm light source for 30 seconds until fully cured. The resulting hydrogel was named PLAm-DAC5.
[0033] 5) Preparation of electro-controlled drug release metal-organic framework composite patches The operation is the same as in Example 1.
[0034] The UiO@SWCNT and UiO-N prepared above + Structural tests were performed using @SWCNT, MOF@Dex, MOF@FLS, and MOF@DS, and the results are as follows: Figure 1 For UiO@SWCNT, UiO-N + X-ray diffraction patterns of five MOF powders: @SWCNT, MOF@Dex, MOF@FLS, and MOF@DS. The positions of the diffraction peaks indicate the successful preparation of UiO-N⁺@SWCNT. After adsorption of anionic drugs, its X-ray diffraction pattern did not change significantly.
[0035] Figure 2 The transmission electron microscope (TEM) images of the above MOF powders show that SWCNTs were successfully attached to UiO.
[0036] Figure 3 The above are Zeta plots of MOF powders. Compared to UiO@SWCNT, UiO-N + The Zeta potential of @SWCNT becomes positive, indicating that N-methylation introduces electronic defects into the framework. When UiO-N + After @SWCNT adsorbs anionic drugs, the Zeta potential decreases, indicating a coulombic interaction between the drug anionic and cationic frameworks.
[0037] Figure 4 The N2 adsorption-desorption isotherms of the above MOF powders show that, after N-methylation modification, the specific surface area of UiO@SWCNT increases from 566.09 m² / s². 2 / g decreased to 172.53 m 2 / g, verifying the approach of introducing pyridinyl N-methyl groups into the linkers and TfO- into the pores to reduce porosity. After loading the drug, the specific surface area decreased to approximately 30 m² / g. 2 / g indicates that the drug is effectively loaded into UiO-N + @SWCNT
[0038] As Figure 5 shown, the antibacterial hydrogel P(PLMA-AM-DAC) prepared by the present application is connected with a mobile phone APP through a Bluetooth module and a flexible circuit board (FPC) to construct an integrated electric stimulation transdermal drug delivery patch.
[0039] The MOF material and the hydrogel prepared above are subjected to the following performance tests:
[0040] Test Example 1 UiO-N + @SWCNT electrochemical performance characterization The electrochemical performance of the UiO-N + @SWCNT electrode prepared in Example 1 is evaluated by using an electrochemical workstation, and the specific content is as follows: cyclic voltammetry test is carried out in a three-electrode system with 0.01M phosphate buffer solution as electrolyte. As Figure 6 shown, compared with UiO@SWCNT, UiO-N + @SWCNT observed a pair of obvious redox peaks in the potential window of-1.2V to 1V, the anodic peak was-0.12V, and the cathodic peak was-0.51V (relative to Ag / AgCl), which can be attributed to the transition between the cationic and neutral forms of the electron-deficient bipyridine site.
[0041] Test Example 2 UiO-N + @SWCNT / Drug electro-controlled drug release performance test According to the CV curve of UiO-N + @SWCNT, two voltages of-0.6V and-1V are selected for electrostimulation drug release research. The series of UiO-N + @SWCNT / Drug (MOF@Dex, MOF@FLS, MOF@DS) are made into electrodes, and given electrostimulation (ES) by using an electrochemical workstation. As Figure 7 can be seen from b in the above table, the release amount at-0.6V is better than that at-1V, which may be due to the instability of the electrolyte caused by the higher voltage, which damages the drug release process. Therefore, -0.6V is selected as the best stimulation voltage for drug delivery in this system. As Figure 7As shown in c, the MOF@Drug can be flexibly controlled by the "on-off" of ES. When ES is applied, a linear release profile of diclofenac sodium is observed; when ES is off, almost no diclofenac sodium is released. Dexamethasone sodium phosphate can be dissociated in PBS electrolyte due to the presence of phosphate, so there is a small amount of dexamethasone sodium phosphate released when ES is off. However, a continuous stimulation of -0.6 V for 10 min can release 239 μg / mg of dexamethasone sodium phosphate; while soaking for 10 min only releases 15 μg / mg, indicating that ES enables more dexamethasone sodium phosphate to be released at a higher potential.
[0042] Test Example 3 Antibacterial performance of P(PLMA-AM-DAC) hydrogel The antibacterial performance of the hydrogel was evaluated using the spread plate method. The contact inhibition effect of the hydrogel on bacteria was evaluated by co-culturing with E. coli (gram-negative) and S. aureus (gram-positive), respectively. 50 μL of pre-polymerized hydrogel solution was added to a 96-well plate and irradiated under a UV-LED 405 nm light source for 30 s to completely solidify. 10 μL of bacterial suspension (10 7 CFU·mL -1 ) was added to the surface of the fully gelled hydrogel, and the bacterial solution was evenly dispersed on the gel surface by gentle shaking, then placed in a 37°C incubator for 2 h. After incubation, the hydrogel was taken out, 100 μL of 0.01M PBS was added to the well plate to resuspend the bacteria, and the process was repeated 5 times. The bacterial suspension was collected, 100 μL of which was diluted 10 times, and then 100 μL of the bacterial suspension was plated (LB medium), and incubated at 37°C for 18 h before taking a photo for counting. In addition, the integrity and morphological structure of the bacterial membrane were observed by scanning electron microscopy (SEM). The bacterial suspension of different treatment groups was centrifuged at 5000 rpm for 20 min. Then the obtained small balls were fixed with 4% paraformaldehyde at 4°C overnight. The fixed samples were washed with PBS several times, and then dehydrated in a series of ethanol solutions with different concentrations (20%, 40%, 60%, 80%, 100%) for 10 min. Finally, 10 μL of the dehydrated bacterial sample was imaged and analyzed by SEM for the morphology of all samples.
[0043] The PLAm hydrogel showed an antibacterial rate of 86.5% for E. coli and 93.0% for S. aureus within 2 h; the PLAm-DAC2 showed a high antibacterial effect on E. coli (99.6%) and S. aureus (97.7%) due to the synergistic effect of PLMA and DAC (b in Figure 8 To visually investigate the antibacterial effect of the hydrogel, SEM imaging of the bacteria was performed (c in Figure 8c) in Fig. 1. The E. coli and S. aureus of the control group maintained smooth and intact structure. In contrast, the bacteria co-cultured with the hydrogels exhibited a wrinkled and ruptured morphology of the membrane, indicating that the PLAm-DAC2 hydrogel could effectively destroy the bacterial membrane and thus had antibacterial activity.
[0044] Test Example 4 Cell compatibility of hydrogels and powders The cell compatibility of the nanomaterials UiO@SWCNT, UiO-N + @SWCNT, MOF@FLS, MOF@Dex, and MOF@DS was investigated using mouse L929 fibroblasts. The L929 cells were cultured in a culture medium supplemented with 10% fetal bovine serum (FBS, Promocell) and 1% double-antibiotic. The L929 cells (1 x 10 4 cells per well) were seeded in a 96-well plate and cultured for 24 h to allow them to adhere and spread completely. Then, the culture medium containing different concentrations of nanomaterials was added. After 24 h of culture, CCK-8 reagent was added, and the OD value was read using an enzyme-labeled instrument to measure the absorbance at 450 nm.
[0045] Calculation formula: Cell viability (%) = (A s -A b1 ) / (A c -A b2 ) x 100%; A s : absorbance of the experimental well (including cells, culture medium, CCK-8 solution, and drug solution); A c : absorbance of the control well (containing cells, culture medium, and CCK-8 solution, but not containing drugs); A b1 : absorbance of the drug background well (including culture medium, CCK-8 solution, and drug solution, but not including cells); A b2 : absorbance of the blank background well (including culture medium and CCK-8 solution, but not including cells and drugs).
[0046] The sterile hydrogels were soaked in a culture medium containing 10% FBS for 72 h, and the extraction concentration was set to 0.1 g mL-1. L929 cells (1 x 10 4 cells per well) were seeded in a 96-well plate with 10-fold diluted hydrogel extract, and cultured for 24 h. The CCK-8 test method was used to test the cytotoxicity of the hydrogel extract.
[0047] First, the cytotoxicity of different concentrations of the series of MOFs on mouse fibroblasts (L929) was evaluated by CCK-8 experiment. As shown inFigure 9 As shown in a of FIG. 10, the viability of L929 cells treated with MOFs was higher than 70% at a concentration of 100 μg / mL, indicating that the toxicity of MOFs to L929 cells was negligible.
[0048] At the same time, the cytotoxicity of L929 cells treated with different concentrations of PLAm, PLAm-DAC2 and PLAm-DAC5 hydrogel extracts was evaluated by CCK-8 experiment. Figure 9 As shown in b of FIG. 10, the cell viability of the PLAm-DAC2 group had no significant difference from that of the control group. The above results prove that the hydrogel has no cytotoxicity to fibroblasts and has good biocompatibility.
[0049] Test Example 5 Treatment effect of electrically controlled drug release metal organic framework-based composite patch on psoriasis Male 6-8 week-old BALB / c mice were selected to compare the treatment effects of different treatments on psoriasis. The experimental groups were: a blank control group (Normal), a model control group (IMQ), a positive control group (Dex), a PLAm-DAC2 gel group (Gel), and a PLAm-DAC2 gel+MOF@Dex electrode+ES group (Patch), with 8 mice in each group.
[0050] Modeling: After 3 days of adaptive feeding, the BALB / c mice were anesthetized by intraperitoneal injection of 1.5% sodium pentobarbital 40 mg / kg, and the experimental area (about 2 cm x 3 cm) on the back of all the mice was depilated. A 5% imiquimod (IMQ, Mingxin Pharmaceutical) induced psoriasis mouse model was used. Except for the Normal group, the mice in the other groups were given 5% imiquimod cream 65 mg on the experimental area on the back every day for 7 consecutive days.
[0051] Treatment process: After 2 hours of 5% IMQ application, the mice in the remaining three groups were given Dex solution (0.5 mg / mL, 100 μL), PLAm-DAC2+MOF@Dex (without electrical stimulation), and PLAm-DAC2+MOF@Dex+ES (Patch) (daily electrical stimulation: -0.6 V, 10 min) treatment, respectively, and were fixed with 3M patches. The mice in each group were weighed and photographed every day, and the PASI score (erythema, infiltration, scaling, and total PASI score) was calculated. After 7 days, the mice were sacrificed, and the skin tissue and spleen were obtained. The skin was fixed in 4% paraformaldehyde. In the histological analysis, the skin tissue sections were stained with H&E, and the condition of the skin and the infiltration of inflammatory cells were observed and analyzed.
[0052] As Figure 10a), repeated topical application of imiquimod (IMQ) cream on the dorsal skin of mice for 7 consecutive days induced skin lesions such as erythema, scaling, induration and increased skin fold thickness. Compared with the model group (IMQ group), gel group (Gel), Dex solution group, the application of the composite patch (Patch group) treatment greatly improved the severity of imiquimod-induced psoriasis symptoms. During the treatment, the therapeutic effect of Dex and Gel groups was not obvious, because in the Dex solution group, only a small amount of drug can penetrate the skin, and in the Gel group, there is no electric stimulation, only 10-20 μg of Dex is released from the MOF@DEX. These results show that the composite patch Patch can achieve controlled drug release under the action of electric stimulation, with high drug utilization rate and good therapeutic effect. The severity of the disease was evaluated every day using the objective scoring system based on the Psoriasis Area and Severity Index (PASI), including erythema, scaling and induration (Fig. 1 Figure 10 b). According to the PASI score, Patch showed the best therapeutic effect. Imiquimod can induce significant enlargement and weight gain of the spleen, which is attributed to the release of inflammatory cytokines such as Figure 10 c), the spleen of the Patch composite patch treated mice showed similar spleen weight and size as the normal group. No significant changes in body weight were monitored during the treatment, as shown in Fig. 1 Figure 10 d, which means the safety of the Patch composite patch.
[0053] Skin histopathology is the most intuitive evaluation standard for psoriasis. Comparing the hematoxylin and eosin (H&E) stained skin tissue section photos (Fig. 1 Figure 11 a), compared with the IMQ group, the epidermal proliferation and inflammatory cell infiltration of the composite patch Patch treatment group were significantly reduced. As shown in Fig. 1 Figure 11 b), after Patch treatment, the skin showed similar epidermal thickness as the normal group, because the Patch provided a relatively humid environment for the diseased skin during use, and the amount of Dex drug molecules penetrating the skin increased under the promotion of electric stimulation, achieving the best therapeutic effect. However, the Gel group still showed obvious psoriasis symptoms, with an epidermal thickness of 83 μm, and the Dex solution group had an epidermal thickness of 55 μm, still showing psoriasis symptoms.
Claims
1. A method for preparing an electrically controlled drug-release metal-organic framework composite patch, characterized in that, Includes the following steps: 1) Preparation of UiO-N + @SWCNT Single-walled carbon nanotubes, Zr 4+ By combining with 2,2'-bipyridine-5,5'-dicarboxylic acid ester, UiO-67 was in situ grown on SWCNT via a solvothermal method to prepare UiO@SWCNT. Then, the bipyridine moiety was N-methylated with methyl trifluoromethanesulfonate to obtain UiO-N. + @SWCNT; 2) Preparation of UiO-N + @SWCNT loaded with drugs Prepare the drug solution by adding UiO-N + @SWCNT is placed in the drug solution to obtain UiO-N + @SWCNT / Drug; 3) Preparation of UiO-N + @SWCNT / Drug membrane electrode UiO-N + @SWCNT / Drug material and conductive agent are prepared into a slurry in polyvinylpyrrolidone / N-methylpyrrolidone solution, vortexed, and then the slurry is drop-coated onto a polytetrafluoroethylene mold and dried to obtain a membrane electrode. 4) Preparation of P(PLMA-AM-DAC) hydrogel A PBS solution of phenyl (2,4,6-trimethylbenzoyl) lithium phosphate was prepared, and then methacrylamide polylysine, acrylamide and acryloyloxyethyltrimethylammonium chloride were added. After dissolving by shaking at room temperature, the solution was sterilized using a sterile needle filter. The solution was injected into a polytetrafluoroethylene mold and irradiated under a UV-LED light source until it was completely cured to obtain P(PLMA-AM-DAC) hydrogel. 5) Preparation of electro-controlled drug release metal-organic framework composite patches UiO-N + The @SWCNT / Drug membrane electrode is attached to the P(PLMA-AM-DAC) hydrogel, and then covered with a flexible printed circuit board to assemble an electro-controlled drug release metal-organic framework composite patch.
2. The preparation method of the electro-controlled drug release metal-organic framework composite patch according to claim 1, characterized in that, The drugs include conventionally loadable small molecule anionic drugs.
3. The preparation method of the electro-controlled drug release metal-organic framework composite patch according to claim 1, characterized in that, The drug includes one or more of dexamethasone sodium phosphate, fluorescein sodium, and diclofenac sodium.
4. An electro-controlled drug release metal-organic framework composite patch obtained by the preparation method according to any one of claims 1-3, characterized in that, It is a P(PLMA-AM-DAC) hydrogel, UiO-N + The composite dressing is formed by sequentially assembling the @SWCNT / Drug membrane electrode and the flexible printed circuit board.
5. The use of the electro-controlled drug release metal-organic framework composite patch of claim 4 in the preparation of a psoriasis treatment product.
Citation Information
Patent Citations
Drug-loaded mixed conductive hydrogel, preparation method and temperature / electrical stimulation bimodal drug controlled release patch
CN117982411A
Preparation method and application of multifunctional metal organic framework nanoparticles
CN118649248A
Sequential controlled-release double-drug-loaded injectable hydrogel as well as preparation method and application thereof
CN118902984A
High-performance photocatalytic metal organic framework antibacterial material as well as preparation method and application thereof
CN119456031A
Metal organic framework composite film based on thermoelectric effect, flexible temperature sensor and preparation method of flexible temperature sensor
CN120424384A
